Demystifying Dutch Disease - Kojo, Naoko C. (World Bank Group, Washington, DC, 2014)
This paper examines the theory of Dutch disease and its implications for practical policy questions. Dutch disease is a term that is well-known to economists and development practitioners. But it is also a concept that is often conflated with "resource curse" and misinterpreted as a "disease" that necessarily causes adverse impacts on the economy. The paper points out that many of the seemingly well-established arguments in this field are not necessarily grounded in theory or empirical evidence. Great care is needed in diagnosing Dutch disease and formulating policy prescriptions based on the theoretical framework, given the restrictive assumptions that may not be fully applicable and the limited relevance to today s inextricably intertwined trade flows. Countries facing large inflows of foreign currency should focus on safeguarding the domestic economy from the volatility of international commodity and capital markets, and building robust institutions to reduce adjustment costs and boost broader competitiveness. A policy package needs to be comprehensive, covering macroeconomic and structural policy measures, and should be calibrated to target country specific concerns. Policies may need to be adjusted continuously in view of the evolving dynamics of the global and domestic economic environment.